The Influence of Green Product, Green Marketing, and Brand Image on Consumer Purchasing Decisions of Bottled Water - Ignatius Agus Suryono; Abdurrazak Alfan; Sudaryatie Sudaryatie (UniSadhuGuna Business School, 2023)
As time progresses, accompanied by the rapid advancement of technology, the awareness and concern of society regarding the importance of preserving the environment has increased. The environmental awareness movement, promoted by both the government and initiatives from society, has begun to be campaigned throughout Indonesia. Business actors as producers who generate various types of waste that have the potential to disrupt environmental sustainability now need to implement the concepts of sustainability and eco-friendliness. Changes in the lifestyle of society, which currently tends to be practical and instant, have resulted in the emergence of various products that support these desires. The bottled water industry in Indonesia has experienced growth and development from year to year. Looking at the various phenomena above, many companies have gradually shifted to using environmentally friendly raw materials for their products. The study was conducted through a survey using a questionnaire as a data collection tool. The population and sample in this study are 128 consumer students from FEB UPN